2005
DOI: 10.1097/01.gme.0000141760.98678.ed
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms associated with thrombophilia and vascular homeostasis and the timing of menarche and menopause in 728 white women

Abstract: We identified various genetic and personal history parameters influencing age at natural menopause and the risk of undergoing premenopausal hysterectomy. To the best of our knowledge, we present the largest study to date determining SNPs as contributors to the genetic control of the timing of natural and surgical menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 29 publications
(46 reference statements)
1
29
0
Order By: Relevance
“…Our results showed that ApoE ε4 is associated with a delayed age at menopause, suggesting that ApoE ε4 carriers may have a longer reproductive period, which is important for reproductive function, and will thus have had an advantage in ancient times. Previously, Tempfer et al (2005) found that ApoE 158SNP was significantly associated with ANM (P= 0.03) and ApoE 112SNP was associated with age at menarche (P=0.06) in white women. Koochmeshgi et al (2004) first reported that carriers of ApoE ε4 reached menopause at an earlier age (P=0.049) in the Iranian population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that ApoE ε4 is associated with a delayed age at menopause, suggesting that ApoE ε4 carriers may have a longer reproductive period, which is important for reproductive function, and will thus have had an advantage in ancient times. Previously, Tempfer et al (2005) found that ApoE 158SNP was significantly associated with ANM (P= 0.03) and ApoE 112SNP was associated with age at menarche (P=0.06) in white women. Koochmeshgi et al (2004) first reported that carriers of ApoE ε4 reached menopause at an earlier age (P=0.049) in the Iranian population.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ApoE may play a role in the regulation of the steroid hormone system and influence human reproduction (Finch and Sapolsky 1999). However, only a few studies have reported an association between ApoE polymorphisms and age at natural menopause (ANM) (Koochmeshgi et al 2004;Tempfer et al 2005;van Disseldorp et al 2008;He et al 2009b). The present study aimed to investigate the possible association of ApoE genotype with age at menarche and menopause in Chinese females.…”
Section: Introductionmentioning
confidence: 99%
“…To replicate previous findings, we compiled a list of SNPs previously associated with age at menopause in women with European ancestry. These SNPs included 15 SNPs discovered in GWAS with P-values ,10 27 (distributed across five loci), nine SNPs with P-values between 10 24 and 10 27 (distributed across nine loci), 17 SNPs discovered by a GWAS meta-analysis (distributed across 17 loci, of which 16 were novel) and seven SNPs implicated in candidate gene studies (distributed across six loci) (17)(18)(19)(27)(28)(29)(30)(31)(32)(33). The LD relationships among the SNPs in HapMap CEU in each region were carefully examined to determine the effective number of tests.…”
Section: Meta-analysismentioning
confidence: 99%
“…Several candidate gene studies in women with European ancestry identified seven SNPs located in six loci (F5, CYP1B1, ESR1, AMHR2, HSDB1, APOE) as associated with age at menopause (27)(28)(29)(30)(31)(32)(33). We investigated whether these SNPs are also associated with this trait in African-American women.…”
mentioning
confidence: 99%
See 1 more Smart Citation